Approaches to classifying and restoring degraded tropical forests for the anticipated REDD+ climate change mitigation mechanism - Sasaki, N.; Asner, G.P.; Knorr, W.; Durst, P.B.; Priyadi, H.; Putz, F.E. (Italian Society of Sivilculture and Forest Ecology (SISEF), 2011)
Inclusion of improved forest management as a way to enhance carbon sinks in the Copenhagen Accord of the United Nations Framework Convention on Climate Change (December 2009) suggests that forest restoration will play a role in global climate change mitigation under the post-Kyoto agreement. Although discussions about restoration strategies often pertain solely to severely degraded tropical forests and invoke only the enrichment planting option, different approaches to restoration are needed to counter the full range of degrees of degradation. We propose approaches for restoration of forests that range from being slightly to severely degraded. Our methods start with ceasing the causes of degradation and letting forests regenerate on their own, progress through active management of natural regeneration in degraded areas to accelerate tree regeneration and growth, and finally include the stage of degradation at which re-planting is necessary. We argue that when the appropriate techniques are employed, forest restoration is cost-effective relative to conventional planting, provides abundant social and ecological co-benefits, and results in the sequestration of substantial amounts of carbon. For forest restoration efforts to succeed, a supportive post-Kyoto agreement is needed as well as appropriate national policies, institutional arrangements, and local participation.